UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR MELALUI METODE DISCOVERY BAGI SISWA KELAS VI SDN 11 KOTA KULON - Ida Farida; Teti Nurmayati; Rosidah (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The purpose of this study is to implement the discovery method to improve learning outcomes in the subject matter of flat shapes and the activities of class VI students at SDN 11 Kota Kulon in the 2018/2019 academic year and teacher performance? This classroom action research aims to determine the increase in learning outcomes in the subject matter of flat shapes and the activities of class VI students at SDN 11 Kota Kulon in the 2018/2019 academic year and teacher performance through the implementation of the discovery method. This research was conducted at SDN 11 Kota Kulon which is located at Jalan Jendral Sudirman No Blk. No. 5. The research subjects were class VI students at SDN 11 Kota Kulon in the 2018/2019 academic year, totaling 40 students consisting of 20 male students and 20 female students, two teachers, one as a researcher and one as an observer. This research is a classroom action research carried out in two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The data taken was in the form of data from student observations, teacher observations, end-of-cycle evaluation tests and data from student reflection questionnaire results on learning. The results showed that in cycle I the average score of student learning outcomes was 60.75 with the lowest score being 30 and the highest score being 90.00 and students who obtained a minimum score of 65 and above there were 14 students (35%). Whereas in cycle II an average score of 76.63 was obtained with a lowest score of 30 and a highest score of 100 and students who obtained a minimum score of 65 and above there were 32 students (80%). The results of observations of teachers showed that in the first cycle the teacher was not able to manage time properly and the learning process was not effective. But in cycle II the teacher was able to manage time well and the learning process was effective. The conclusion that can be drawn is that through the implementation of the discovery method it can improve learning outcomes of the subject matter of flat shapes and the activities of class VI students at SDN 11 Kota Kulon in the 2018/2019 academic year and teacher performance. For this reason, it is suggested to the teachers of SDN 11 Kota Kulon to implement the discovery method on the subject matter of flat shapes.